Tingkat Kepuasan Keluarga Pasien Rawat Inap Peserta Program BPJS Kesehatan Berdasarkan Status Kepesertaan - Ovie Lestya Nurdiana; Menap Menap; Lalu Abdul Khalik; Nova Budiharjo; Sismulyanto Sismulyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the difference in the level of family satisfaction of BPJS PBI and non-PBI patients in the inpatient room at Mutiara Sukma Hospital, NTB. This research is a quantitative research using a cross-sectional approach. The results of this study indicate that there is no difference in the level of family satisfaction of BPJS PBI and BPJS non-PBI patients. Based on the IKM value, the level of family satisfaction of non-PBI BPJS patients is higher than that of BPJS PBI. Still, based on statistical tests using Mann-Whitney, it shows that there is no significant difference between family satisfaction of BPJS PBI patients and BPJS non-PBI patients (p = 0.698). In conclusion, overall, there is no difference in the level of family satisfaction of BPJS PBI and non-PBI patients. Keywords: BPJS, Health Insurance, Satisfaction